Pengembangan Model Pembelajaran Contextual Teaching and Learning untuk Meningkatkan Kreativitas Siswa - Siti Fatmawati (Bidayatuna, 2018)
The learning model is one of the requirements in improving student learning, not only in matters relating to student interest in class, but also in student creativity in following the learning process. One of the learning models that is currently trending is contextual teaching and learning.